Inpatient Psychiatric Rehabilitation: An Alternative to Bringing Back the Asylum - Reinhardt, Dawn L. (International Journal of Psychosocial Rehabilitation, 2016)
Recent recommendations by medical ethicists advocate for the return of asylums to improve long-term psychiatric care for individuals who have treatment refractory psychiatric conditions. Long-term inpatient psychiatric hospital environments are not conducive to learning tenancy and recovery skills necessary for optimal community integration. Psychiatric rehabilitation and alternative community interventions provide greater opportunities for learning practical and recovery- oriented skills. Increasing evidence-based psychiatric rehabilitation interventions in the inpatient setting while adequately funding community-based service options is a better alternative. Returning to the asylum-model of long-term psychiatric treatment will harm advances made in the field of psychiatric rehabilitation and the reduction of stigma.